Make-Up Business Performance through Company Strategic Goal Setting Using Balanced Scorecard - Beinargi, Ahzam (Soegijapranata Catholic University, 2025)
Emulation of frozen vegetables progress competitively because of excelsior. Applying vision, mission, and strategy are absolute matters which must be possessed by. Vision and mission of is still not yet be comprehended by employees much.PT Kelola Agro Makmur encountered competition and potency due to social awareness of important healthy food. Its problems in measuring performance that still relies on earnings as performance indicator and has not used the basic strategy that comprehended by employees yet. The company must work on direction to maximize its performance. Goal setting of strategy used balanced scorecard is easier conducted by assisting BSC Designer. This research is descriptive qualitative. It uses primary data gathered from structured interview, participative observation, and company data documentation. The result of research shows four target strategy: finance, customer, internal business, study and development. It is used indicator and monitoring of BSC Designer to measure the performance business.